1994
DOI: 10.1073/pnas.91.2.822
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity of hepatocellular carcinoma.

Abstract: We studied 80 hepatocellular carcinomas from three continents for p53 gene (TP53) mutations and hepatitis B virus (HBV) sequences. p53 mutations were frequent in tumors from Mozambique but not in tumors from South Africa, China, and Germany. Independent of geographic origin, most tumors were positive for HBV sequences. X gene coding sequences of HBV were detected in 78% of tumors, whereas viral sequences in the surface antigen-and core antigen-encoding regions were present in less than 45% of tumors. These obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(61 citation statements)
references
References 23 publications
1
60
0
Order By: Relevance
“…[65][66][67][68] HBx variants expressed from the chromosomally integrated mutants may also contribute to different HBx distribution patterns and expression levels, particularly in the neoplastic lesions. Combined use of several antibodies recognizing different epitopes, as in this study, should greatly increase the possibility to detect HBx in the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[65][66][67][68] HBx variants expressed from the chromosomally integrated mutants may also contribute to different HBx distribution patterns and expression levels, particularly in the neoplastic lesions. Combined use of several antibodies recognizing different epitopes, as in this study, should greatly increase the possibility to detect HBx in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…78,80,81 In this study, we observed a close statistical correlation between expression of HBx and existence of HBsAg in HCC-bearing liver, which may reflect the frequent preservation of the X gene together with the PreS2/S1 region during the integration of HBV DNA into cellular genomic DNA and the following rearrangements. [65][66][67][68] However, their distribution patterns were differ- ent. Our results demonstrated that the expression of HBx, among the three HBV antigens examined, was preferentially maintained through the multistage process from foci and nodules of altered hepatocytes, for which a preneoplastic nature has been demonstrated, 54,57 to HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristics of these tumors and methods for DNA isolation have been described previously [13,14]. SNP309 (T/G) of MDM2 were genotyped using PCR amplification of the first intron of the MDM2, followed by MspA1I (Promega) digestion as described elsewhere [15].…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] Only a few tumor suppressor genes have been implicated in liver carcinogenesis. P53 mutations [5][6][7][8] and Rb-encoding gene rearrangements 9,10 have indeed been shown in HCC tumor tissues. More recently, deletions and mutations have been identified in around 61%, and in up to 26% of HCCs, in the genes encoding the mannose 6-phosphate/insulin-like growth factor II receptor 11,12 and in the ␤-catenin encoding gene, 13 respectively.…”
mentioning
confidence: 99%